2003
DOI: 10.17221/5787-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of and resistance to antimicrobial agents of Bacillus cereus isolates from foodstuffs

Abstract: The study was aimed at the assessment whether foodstuffs contaminated with Bacillus cereus (B. cereus) may concurrently be vectors of spreading resistance. The contamination of foodstuffs with B. cereus strains was found in 31% of dairy and in 28% of meat products tested. Only one product from skimmed milk was contaminated. High-fat milk products that were heat-treated during the technological process (87 samples), as well as heat-treated meat products (65 samples), were contaminated significantly frequently (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
5
23
1
Order By: Relevance
“…In the present study results revealed the incidence of B. cereus isolates as 29.33 per cent in meat and meat products which are in agreement with similar incidence reported by Schlegelova et al, (2003) and Tewari et al, (2013), who too reported an incidence of 28 per cent and 30.9 per cent respectively in meat samples. However, Bedi et al, (2004) and Kamat et al, (1989) reported an incidence of 63.2 per cent and 80 per cent respectively in chicken and meat products.…”
Section: Antibiogram Of B Cereus Isolatessupporting
confidence: 92%
“…In the present study results revealed the incidence of B. cereus isolates as 29.33 per cent in meat and meat products which are in agreement with similar incidence reported by Schlegelova et al, (2003) and Tewari et al, (2013), who too reported an incidence of 28 per cent and 30.9 per cent respectively in meat samples. However, Bedi et al, (2004) and Kamat et al, (1989) reported an incidence of 63.2 per cent and 80 per cent respectively in chicken and meat products.…”
Section: Antibiogram Of B Cereus Isolatessupporting
confidence: 92%
“…B. cereus was recovered from 28 % of the meat products samples including heat-treated products. Of these food samples, heat treated meat products alone showed 48 % positivity for the B. cereus (Schlegelova et al 2003). This is because bacteria are resistant to heat stress.…”
Section: Meat and Meat Productsmentioning
confidence: 97%
“…On the other hand B. cereus and L. monocytogens are also Gram-positive bacteria like S. aureus but they are more resistant to carvacrol microemulsion Table 2 . That could be due to the spore forming nature of B. cereus or the presence of specific antimicrobial drug resistant genes in this microorganism 57 and in L. monocytogens 58,59 which are not present in S. aureus. Table 3 showed that formulation of carvacrol in microemulsion using the cationic surfactant CPC had significantly higher antibacterial activity than that formulated with the non-ionic T20.…”
Section: Antimicrobial Activity Of Carvacrol Microemulsionmentioning
confidence: 99%